Analysis of Social Perception of the Tegaren Community on the Progress of Tourism Village - Joko Mijiarto; Rusdi Hidayat; Budi Prabowo; Firdaus Nuryananda; Praja Firdaus Nuryananda (Nusantara Science and Technology Proceedings, 2022)
This research is also a follow-up to the research with the same scheme in 2021, entitled "Local-Based Empowerment: Tourism Village Development and Local Village Women's Empowerment". In addition, the team from UPN "Veteran" Jawa Timur has helped the development of tourist villages in Tegaren Village through the preparation of the Tegaren Tourism Master Plan 2019-2031. So, this research, in addition to examining the development of Trenggalek Regency to develop its tourism sector, will also discuss the perception of the people of Tegaren about the progress of their tourism village which has been supported by the Tegaren Tourism Master Plan. This will be the main indicator for the research team to carry out a follow-up plan for the preparation of the Tegaren Tourism Master Plan document. The specific objectives of this research are twofold, namely 1) to find and further examine the perception of the people of Tegaren about the progress of their tourist village and 2) to formulate and apply a follow-up plan (RTL) for the development of the Tegaren tourism sector based on the Master Plan document. This research is the embodiment of the UPN "Veteran" Jawa Timur’s Research and Community Service Strategic Plan 2021-2026. This research is in line with one of the six main themes of the research and community service program in 2022, namely tourism. In addition, this research also pays attention to the linearity of the themes of national research and community service programs, namely economic recovery and tourism development. On a regional and regional scale, this research also supports the RIPPDA of Trenggalek 2017-2031 in the tourism sector. The outputs of this research are 1) scientific journals/articles to be published in periodicals and 2) oral and poster presentations at the International Seminar of Research Month event. Theories and concepts used in this study are the theory of community social perception, asset-based community development, community based tourism, and sustainable tourism. This research will be carried out in three stages, namely the preparation stage, the field study implementation stage and the evaluation stage. This research uses descriptive-exploratory research. In this study, the data collection techniques used were literature studies, interviews, questionnaires, and observations. While the data analysis used qualitative data analysis techniques. This research also involves 5 students who will later be converted into the MBKM program with recognition of 20 credits. The temporary results achieved are the satisfaction of the people of Tegaren with the progress of their tourist village. This satisfaction was obtained through interviews with stakeholders in Tegaren.